024 Spectrum and significance of CMR findings in cardiac transthyretin amyloidosis. (3rd April 2017) - Martinez-Naharro, Ana; Treibel, Thomas A; Abdel-Gadir, Amna; Bulluck, Heerajnarain; Zumbo, Giulia; Knight, Daniel S; Kotecha, Tushar; Francis, Rohin; Hutt, David; Rezk, Tamer; Rosmini, Stefania; Quarta, Cristina; et al.
Abstract : Background: Cardiac transthyretin amyloidosis (ATTR amyloidosis) is an increasingly recognised cause of heart failure. Cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE) and T1 mapping is emerging as a reference standard for diagnosis and characterisation of cardiac amyloid. Objectives: We used CMR with extracellular volume fraction (ECV) measurement to characterise cardiac involvement in relation to outcome in ATTR amyloidosis. Methods: Subjects comprised 263 patients with cardiac ATTR amyloidosis corroborated by grade 2–3 99m Tc-DPD cardiac uptake, 17 with suspected cardiac ATTR amyloidosis (grade 1 99m Tc-DPD) and 12 asymptomatic individuals with amyloidogenic transthyretin (TTR) mutations. Fifty patients with cardiac AL amyloidosis acted as disease controls. Results: In contrast to AL amyloidosis, asymmetric septal hypertrophy was present in 79% of ATTR patients (70% sigmoid septum and 30% reverse septal curvature), whilst symmetric left ventricular hypertrophy (LVH) was present in only 18%; 3% of patients has no LVH. In patients with cardiac amyloidosis, the pattern of LGE was always typical for amyloidosis (29% subendocardial, 71% transmural) including right ventricular LGE (96%). 65 patients died during follow-up (19±14 months). ECV independently correlated with mortality and remained independent after adjustment for age, N-terminal pro-brain natriuretic peptide, ejection fraction, E/E' and left ventricular mass index (hazard ratio, 1.164; 95% confidence interval, 1.066–1.271; p<0.01). Conclusions: Asymmetric hypertrophy, traditionally associated with hypertrophic cardiomyopathy, is the commonest pattern of ventricular remodelling in ATTR amyloidosis. LGE imaging is typical in all patients with cardiac ATTR amyloidosis. ECV correlates with amyloid burden and provides incremental information on outcome even after adjustment for known prognostic factors.